Adjusting to external shocks in small open economies: The case of Honduras - Morley, Samuel; Piñeiro, Valeria (International Food Policy Research Institute, 2015)
Like the other small economies of Central America, the economy of Honduras is a challenge for all those searching for an adequate and sustainable growth strategy. After growing strongly for the two decades prior to 1980, the economy suffered through more than 20 years of growth so slow that only in 1998 did per capita income surpass the level it had reached in 1980. Then things seemed to change. For five years (2004–2008) the economy grew by an average of almost 6 percent per year, a performance unmatched since the late 1970s. But then the world financial crisis of 2009 put an end to the boom and pushed Honduras into recession. While the economy subsequently recovered, it has never come close to the growth rates of the early 1990s. Indeed, the growth rate appears to have settled back to around 3.3 percent, enough to produce only a slight increase in per capita income. In this paper we address several growth-related questions. First, what are the drivers of growth, how have they changed, and are the changes related to the cyclic nature of growth in Honduras? Second, how important are negative exogenous balance-of-payments shocks in explaining the many periods of lackluster growth? Third, what can policymakers do to offset the exogenous external shocks and increase the growth rate? We rely on several fundamental inputs in addressing these questions: first, observed patterns of sectoral growth and their changes over time; second, changes in two key determinants of growth, capital and the capacity to import; and third, changes in important exogenous variables such as the real exchange rate and the terms of trade. Finally we develop and present a model of the economy with which we will simulate the impact of various exogenous shocks as well as the policy responses to ameliorate or offset the effect of negative shocks.